PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS - Muhammad Amrillah Aziz; Sri Cacik; Eko Baktiono (STKIP Subang, 2026)
This research is motivated by the low critical thinking skills of students in the Natural and Social Sciences (IPAS) subject, specifically regarding cultural diversity and local wisdom. The learning process tends to be conventional and teacher-centered, causing students to be less trained in analyzing contextual problems. This study aims to describe the steps for implementing the Problem Based Learning (PBL) model and to measure the improvement in critical thinking skills of class IV-B students at UPT SD Negeri Latsari Tuban. This type of research is a collaborative Classroom Action Research (PTK) adopting the Kemmis & Mc Taggart spiral design model. The research was conducted in two cycles. The research subjects were 25 students. Data were collected through essay tests, observation, and interviews. The results showed that the application of the PBL model significantly improved students' critical thinking skills. The percentage of classical learning completeness increased from 40% in the Pre-Cycle to 64% in Cycle I, and reached 88% in Cycle II. The conclusion of this study is that the implementation of the PBL model with contextual issues is proven effective in facilitating and improving the critical thinking skills of elementary school students.